Governance challenges and innovations: financial and fiscal governance - Anheier, Helmut K. (Oxford Univ. Press, 2013)
pt. I Introduction -- 1. Governance: Issues and Frameworks / Helmut K. Anheier and Regina A. List -- pt. II Financial and Fiscal Governance -- 2. Financial and Fiscal Governance: An Introduction / Mark Hallerberg -- 3. Picking Up (and Rearranging) the Pieces: The Politics of Global Financial Governance in the Wake of the Great Recession / Mark S. Copelovitch -- 4. Is European Union Governance Ready to Deal with the Next Financial Crisis? / Lucia Quaglia -- 5. The Fiscal Policy Implications of Balance of Payments Imbalances / Stefanie Walter -- 6. The Political Sources of Crisis Situations / William Roberts Clark and Vincent Arel-Bundock -- pt. III Governance Innovations -- 7. The Contribution of Innovation Research to Understanding Governance Innovation: A Review / Helmut K. Anheier and Mark T. Fliegauf -- 8. Financial Governance Through the Lens of Innovation / Helmut K. Anheier and Mark T. Fliegauf -- pt. IV Governance Indicators -- 9. Governance Indicators: Some Proposals / Piero Stanig and Mark Kayser -- 10. Public---Private Sector Relationships, Capture, and Governance Quality / Klaus J. Brösamle -- 11. Governance Beyond the Nation-state: Estimating Governance Indexes at the Subnational and Transnational Level / Piero Stanig
Enth. 10 Beitr
Keywords: Finanzkrise; Kapitalmarktpolitik; Fiskalpolitik